MAHAR MUQADDAM DALAM ALUR ISTINBAT HUKUM AL-SYAFI’I - Istadha, Datul (Irtifaq, 2016)
Before the wedding when the prospective husband applying for his wife's wife often by giving something something. The duty of the prospective husband to give something of value is in the event of aad marriage sebgai dowry. The time of granting the dowry is at the time of the marriage contract and can be agreed whether the payment is given in cash or can be postponed. If a prospective husband presents something before the marriage ceremony and is intended to be a dowry, in al-Shafi'i's line of law after the discovery of the rest of the Book, references can be found as following what the Prophet did when he married Shafiyah.Keyword : Mahar Muqaddam, Istinbat al-Syafi’i, fi’l Nabi